IMPLANTACIÓN CONTABLE Y ANÁLISIS FINANCIERO EN LA EMPRESA DE CERÁMICA RIALTO DE LA CIUDAD DE LOJA, PERIODO DEL 01 DE FEBRERO AL 31 DE MAYO DEL 2014 - Cabrera Guajala, Aurora Ximena (2015)
The work presents the implementation of low comercial accounting CERAMIC COMPANY IN THE CITY OF RIALTO Loja, PERIOD FEBRUARY 01 TO MAY 31 2014. Was performed by political standards, echnical principles and practices governing commercial accounts showing the full accounting business process is analyzed. The thesis has the overall aim of implementing a commercial accounting because it is essential to act decisively in strengthening and utilization of human, material and financial resources enabling the company to have an accurate accounting for instrument development tool. Required to fulfill the goals set in the project first it was determined the weaknesses that the company, then he could sustain this way the issue raised starting with the production of records, books of account, plan and manual accounts according to the business needs and demonstrate how it can control the goods at the time of purchase and sale that allowed the systematization of economic and financial activities based on the technical merits proceeded to the development of each of the accounting procedure whit their respective definitions The proper use of accounting in the store will maintain, orderly, timely, reliable and updated financial information that facilitates obtaining results 5 that are reflected in the financial statements for the respective analysis can be determined firmly and securely share corrective to be developed. Finally there is the most relevant conclusion: applied an accounting process according to the needs of the company that allows you to take proper control of daily activities in period. So with this owner can be more easily established conditions that affect and promote the economy of the company.